Utilization of Social Capital of Persons with Disabilities in Disaster Mitigation in the Lembang Fault Area - Willya Achmad; Nina Kurniasih; Farhan Rifqi; Salma Aulia (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The Lembang Fault stretches 29 kilometers from Ngamprah Padalarang in West Bandung Regency to Palintang Pasirwangi Ujung Berung in Bandung City. Although the last earthquake occurred in the 15th century, approximately 500 years ago, this fault remains active and has the potential to cause future earthquakes. The urgency of this research is to understand and increase the involvement of the entire community in reducing disaster risk in the Lembang Fault area by utilizing inclusive social capital. Furthermore, a problem arises from the lack of a disaster mitigation planning process for people with disabilities. The purpose of this study is to determine how to early predict the decline or improvement of corporate image through employee satisfaction and performance. This research method uses a qualitative approach. This approach was chosen because this study seeks to describe the empowerment and inclusive use of social capital in disaster mitigation in the Lembang Fault area. Qualitative research relies on responses that describe the experiences, meanings, and perspectives of the research subjects. These research subjects, in general, are those deemed relevant to the issue or topic being studied. To gather the required data, researchers sought detailed information and data through observation, in-depth interviews, and documentation studies. The output will be publications in reputable international journals.